Performance of organomineral fertilizer in winter and rainy potato crop - Atalita Francis Cardoso; Regina Maria Quintão Lana; Walyson Soares; Joicy Vitória Miranda Peixoto; José Magno Queiroz Luz (Bioscience Journal, 2017)
The Agata potato is the most important economic sources of food in Brazil. However, fertilization for this crop has been carried out incorrectly, increasing production costs. Thus, the use of organomineral fertilizer reduces the amount of nutrient applied, facilitates the release of nutrients more slowly and brings improvement in the chemical, physical and biological attributes of the soil. The objective of this work was to evaluate the efficiency of organomineral fertilizers rates and comparate with mineral source on the potato crop in differents seasons. The experimental design was in randomized blocks, with five rates and four replications in the winter season. In the harvest of the rainy season the experiment consisted of 6 rates and four replications. Treatments were 1629.0; 2444.0; 3258.0; 4073.0; 4887.0 kg ha-1 of the organomineral fertilizer which equals 40; 60; 80; 100 and 120% of the rate in relation to the mineral fertilizer of 2800 kg ha-1 of formulation 03-32-06. There weren`t significant difference of the organomineral fertilizer in relation to the mineral in the total, commercial and special class of tubers in the winter crop. In the harvest of rainy crop, the average total productivity of potato tubers at all rates of organomineral fertilizer was 29 t ha-1, which represents 22% higher than mineral fertilizer. The organomineral fertilizer presented agronomic efficiency for potato cultivation and could replace NPK mineral sources. The 4887.0 kg ha-1 organomineral rate generated higher total yield, commercial and special class of tubers.